Reiteration Formulae for the Real Interpolation Method Including L or R Limiting Spaces. (3rd December 2020) - Doktorski, Leo R. Ya.
Abstract : We consider a real interpolation method defined by means of slowly varying functions. We present some reiteration formulae including so-called L or R limiting interpolation spaces. These spaces arise naturally in reiteration formulae for the limiting cases θ = 0 or θ = 1 . Applications to grand and small Lorentz spaces are given.